2016
DOI: 10.7554/elife.17983
|View full text |Cite
|
Sign up to set email alerts
|

Structures of TorsinA and its disease-mutant complexed with an activator reveal the molecular basis for primary dystonia

Abstract: The most common cause of early onset primary dystonia, a neuromuscular disease, is a glutamate deletion (ΔE) at position 302/303 of TorsinA, a AAA+ ATPase that resides in the endoplasmic reticulum. While the function of TorsinA remains elusive, the ΔE mutation is known to diminish binding of two TorsinA ATPase activators: lamina-associated protein 1 (LAP1) and its paralog, luminal domain like LAP1 (LULL1). Using a nanobody as a crystallization chaperone, we obtained a 1.4 Å crystal structure of human TorsinA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
102
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(113 citation statements)
references
References 60 publications
6
102
0
1
Order By: Relevance
“…LAP1 and LULL1 are type II integral membrane proteins; LAP1 binds to the nuclear lamina and resides in the INM (Foisner and Gerace, 1993), whereas LULL1 localizes throughout the ER (Goodchild and Dauer, 2005; Goodchild et al ., 2015; Vander Heyden et al ., 2009). Both proteins activate Torsin by adopting AAA-like folds in their luminal domains and forming a closely apposed interface with Torsin to complement the Torsin active site (Brown et al ., 2014; Sosa et al ., 2014; Demircioglu et al ., 2016). …”
Section: Introductionmentioning
confidence: 99%
“…LAP1 and LULL1 are type II integral membrane proteins; LAP1 binds to the nuclear lamina and resides in the INM (Foisner and Gerace, 1993), whereas LULL1 localizes throughout the ER (Goodchild and Dauer, 2005; Goodchild et al ., 2015; Vander Heyden et al ., 2009). Both proteins activate Torsin by adopting AAA-like folds in their luminal domains and forming a closely apposed interface with Torsin to complement the Torsin active site (Brown et al ., 2014; Sosa et al ., 2014; Demircioglu et al ., 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shed light on the mechanism by which Torsins’ two distinctively localizing cofactors, the nuclear envelope protein LAP1 (Foisner and Gerace, 1993) and the ER protein LULL1 (Goodchild and Dauer, 2005), activate Torsins’ ATPase activity. Torsin cofactors feature AAA+-like folds that trigger ATP hydrolysis by virtue of an arginine finger-based active site complementation mechanism (Brown et al , 2014; Sosa et al , 2014; Demircioglu et al , 2016; Figure 1A). …”
Section: Introductionmentioning
confidence: 99%
“…Torsin species consistent with a homohexameric assembly were observed via blue native PAGE (Vander Heyden et al , 2009; Jungwirth et al , 2010) while cross-linking and structural studies led to alternative models invoking mixed ring assemblies in a 3:3 (TorsinA:cofactor) stoichiometry (Brown et al , 2014; Sosa et al , 2014) as well as a Torsin-cofactor heterodimer (Demircioglu et al , 2016; Figure 1B, I–III). Potential limitations inherent to several attempts aimed at a determination of the oligomeric state are the use of stabilizing conditions including ATPase-arresting mutations, stabilizing nanobodies, or cross-linking reagents (Brown et al , 2014; Sosa et al , 2014; Demircioglu et al , 2016), each of which does not recapitulate the dynamic situation encountered in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…A recent breakthrough revealed that the INM protein LAP1 and the ER luminal protein TorsinA (Figure 1) are needed for LINC complex-dependent nuclear movement in fibroblasts [34 •• ]. LAP1 is a potent activator of TorsinA, an AAA+ ATPase linked to the movement disorder torsion dystonia [35 • ,36,37 •• ]. Whereas AAA+ ATPases typically unfold or disassemble proteins, the substrates of the LAP1/TorsinA complex are unknown.…”
Section: Coupling the Cytoplasm And Nucleus Via The Linc Complexmentioning
confidence: 99%
“…Torsin1A has a membrane-embedded segment but is not strictly a transmembrane protein. The luminal domains of LAP1 and TorsinA each have an AAA+ related fold that associates to form heterooligomers [35 • ]. The LINC complex comprises SUN domain proteins spanning the INM associated with nesprins spanning the ONM [19,20].…”
Section: Figurementioning
confidence: 99%